IMPROVING THE STUDENTS’ ABILITY TO WRITE DESCRIPTIVE PARAGRAPH THROUGH INTRAPERSONAL INTELLIGENCE STRATEGY - Indrayani Simpuruh (ALGAZALI INTERNATIONAL JOURNAL EDUCATIONAL RESEARCH, 2020)
Abstract: Improving the Students’ Ability to Write Descriptive Paragraph Through Intrapersonal Intelligence Strategy. Improving the Students’ Ability to Write Descriptive Paragraph Through Intrapersonal Intelligence Strategy. This research was aimed at finding out whether or not the use of intrapersonal intelligence strategy improves the ability in writing descriptive paragraph of the second year students of Indonesian junior high school. This research employed a quasi experimental method, with one group pre-test and post-test. The result of this research shows that the students’ post-test score for experimental group was higher than the students’ post-test score for control group. it was proved by the result of post-test mean score of experimental group (80.20) that was higher than the control group (70.l0). It is also proved by the value of t-test which was higher than the value of t-table (4.913>2.000). Based on the finding and discussion of the study, the researcher concluded that Intrapersonal Intelligence Strategy is significant to improve the students writing ability to write descriptive paragraph of the second year students of Indonesian junior high school.Keywords: Intrapersonal intelligence, writing.